2020
DOI: 10.3390/ph13060110
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Lipopeptide Conjugates with High Antimicrobial Activity on Vancomycin-Resistant Enterococci

Abstract: Multidrug-resistant bacteria represent one of the most important health care problems worldwide. While there are numerous drugs available for standard therapy, there are only a few compounds capable of serving as a last resort for severe infections. Therefore, approaches to control multidrug-resistant bacteria must be implemented. Here, a strategy of reactivating the established glycopeptide antibiotic vancomycin by structural modification with polycationic peptides and subsequent fatty acid conjugation to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…According to Galbraith et al, saturated fatty acids with 10 or 12 carbon atoms in chain length in general show the highest antimicrobial efficacy [17]. These findings are in accordance with the results of this study and several studies published previously [18][19][20]. Longer fatty acids were found to form aggregates leading to a reduced antibacterial activity [16].…”
Section: Discussionsupporting
confidence: 93%
“…According to Galbraith et al, saturated fatty acids with 10 or 12 carbon atoms in chain length in general show the highest antimicrobial efficacy [17]. These findings are in accordance with the results of this study and several studies published previously [18][19][20]. Longer fatty acids were found to form aggregates leading to a reduced antibacterial activity [16].…”
Section: Discussionsupporting
confidence: 93%
“…This result is in stark contrast with the finding that, when appending a hexaarginine moiety, the best antibiotic activity was seen for compound 16 , modified at the N-terminus. 154 Both 16 and 17 are non-hemolytic and non-toxic toward liver and kidney cells. Moreover, in vivo mice experiments with 16 and 17 revealed that the compounds reside in the liver for several hours and do not primarily distribute to the kidneys, unlike vancomycin, 153 , 154 a behavior which could alleviate the risk of nephrotoxicity in patients with renal impairment.…”
Section: Recent Developments In Semisynthetic Glycopeptide Antibioticsmentioning
confidence: 99%
“…Muhlberg and coworkers have also explored conjugating triarginine and a fatty acid to various locations on periphery of vancomycin (Figure 2d) (Mühlberg et al., 2020). The most potent vancapticin conjugate, V V ‐R 3 C‐C12, had the peptide and lipid conjugated from the vancosamine handle of vancomycin.…”
Section: Cell Penetrating Peptide Conjugates With Antibioticsmentioning
confidence: 99%